Constructing Ethnolinguistic Identities: A Critical Examination of Language and Power Dynamics in Diasporic Communities - Nuristani , Sarwar; Dadman, Enayatullah; Stanikzai , Sultan Mohammad (Journal Corner of Education, Linguistics, and Literature, 2024)
This research investigates the complex interplay between language and power in the formation of ethnolinguistic identities within diasporic communities. As globalization accelerates, diasporic groups navigate a complex landscape where traditional linguistic practices intersect with new socio-political realities. This study aims to critically examine how language functions as a tool for negotiating identity and power within these communities, emphasizing the role of language ideologies and practices in shaping social dynamics. The primary objectives are to explore how language serves as a medium for the construction and negotiation of ethnolinguistic identities and to understand the influence of power relations on these processes. Specifically, the study seeks to identify the ways in which language practices reflect and challenge power structures within diasporic contexts and how these practices contribute to the formation of collective and individual identities. This research is a multi-sited ethnographic approach,and integrates discourse analysis across several diasporic communities. Findings reveal that language serves as a strategic resource for negotiating social status and ethnic belonging. Diasporic individuals employ code-switching, language reclamation, and multilingualism to assert identity and resist assimilation pressures. The study highlights how language ideologies both reinforce and contest existing power structures, demonstrating the dynamic role of language in shaping ethnolinguistic identities amidst shifting socio-political landscapes.